2021
DOI: 10.1101/2021.06.29.450334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing neural network robustness improves match to macaque V1 eigenspectrum, spatial frequency preference and predictivity

Abstract: Task-optimized convolutional neural networks (CNNs) show striking similarities to the ventral visual stream. However, human-imperceptible image perturbations can cause a CNN to make incorrect predictions. Here we provide insight into this brittleness by investigating the representations of models that are either robust or not robust to image perturbations. Theory suggests that the robustness of a system to these perturbations could be related to the power law exponent of the eigenspectrum of its set of neural … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…We have also reproduced the result of [Kong et al, 2022] that feedforward CNN has a substantially smaller value of a (Fig. 4D) and found that the recurrent CNN model of [Wang and Hu, 2021], which also achieves very high accuracy for image classification, has an even smaller value of a (Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…We have also reproduced the result of [Kong et al, 2022] that feedforward CNN has a substantially smaller value of a (Fig. 4D) and found that the recurrent CNN model of [Wang and Hu, 2021], which also achieves very high accuracy for image classification, has an even smaller value of a (Fig.…”
Section: Resultssupporting
confidence: 80%
“…In-vivo recordings of [Stringer et al, 2019] found that the value of α for primary visual cortex of mouse is actually close to this optimal value α = 1 + 2/ d . This neural coding property of area V1 in the brain has gained additional interest through the contrasting result of [Kong et al, 2022]. They found that feedforward CNNs, which are viewed to be substantially less noise robust than the brain, have in fact a smaller a, as predicted by the theory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like SA, sensory stimuli also activate a diverse set of neural patterns, and various studies have observed tens to hundreds of significant dimensions in flies, zebrafish, mice, and primates (Avitan et al, 2017;Cowley et al, 2016;Kong et al, 2022;Murthy et al, 2008;Stringer et al, 2019a). Many neurons are active during both spontaneous and sensory-driven activity, but it appears that the neurons present in a specific SA pattern are not all driven by the same sensory stimulus.…”
Section: Spontaneous Activity In Many Cases Is Orthogonal To Sensory-...mentioning
confidence: 99%
“…the variance explained by the n th principal component of the covariance matrix scaled as 1/n. In recent work (Kong et al, 2022) observe similar structure in representations from V1 in macaque monkeys and relate robustness to eigenspectrums of neural activations. Put another way, the coefficient of the power law (often denoted α), has been observed close to 1 in biological brains.…”
Section: Introductionmentioning
confidence: 83%